The bridegroom Messiah and the people of God marriage in the Fourth Gospel - McWhirter, Jocelyn (Cambridge Cambridge University Press, 2006)
Many interpreters of the Fourth Gospel detect allusions to biblical texts about marriage, but none offers a comprehensive analysis of these proposed allusions or a convincing explanation for their presence. Building on the work of Richard Hays, Donald Juel and Craig Koester, in this 2006 book Jocelyn McWhirter argues that John alludes to biblical texts about marriage in order to develop a metaphor for Jesus and how he relates to his followers. According to McWhirter, John chooses these texts because he uses a first-century exegetical convention to interpret them as messianic prophecies in light of an accepted messianic text. Specifically, he uses verbal parallels to link them to Psalm 45, a wedding song for God's anointed king. He then draws on them to portray Jesus as a bridegroom-Messiah and to depict Jesus' relationship with his followers in terms of marriage.
Allusions to biblical texts about marriage -- Echoes of scripture, representative figures, and messianic exegesis -- The revelation of the bridegroom-Messiah allusions to Jeremiah 33:10-11 and Genesis 29:1-20 -- The glorification of the bridegroom-Messiah allusions to Song of Songs 1:12 and Song of Songs 3:1-4 -- The bridegroom-Messiah of Psalm 45 in the Song of Songs, Jeremiah 33:11 and Genesis 29:1-20 -- Hearing the echoes -- Conclusion
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Jesus Christ -- Messiahship; Bible -- Criticism, interpretation, etc; Bible -- N.T. -- John -- Criticism, interpretation, etc; Marriage -- Biblical teaching; Jesus Christ ; Messiahship; Bible ; John ; Criticism, interpretation, etc; Marriage ; Biblical teaching